A Differentiation of Gifted and Talented Singers - et.al, Mohd Azharabu Bakar (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This journal purposes on the studies of correct vocal singing techniques and knowledge sharing information. The methodology used in this study was throughacquiring vocal aesthetics and improvisations in singing skills from gifted singers derived through interviewsfromsome of Malaysia’s mostgifted stars.The discovery of this study with regards to theanalysis on the differentiation of vocal characteristic aims to indicate positive and innovative results against negative and stereotype emulated singing of amateur singers.Through the findings of this research, amateur and aspiring new singers shall be able to learn to sing and perform properly. The main findings and results aretabled from the top to the least based on important tips like feel, innovative methods, techniques and creativity invarious singing performances. Practical contribution of this study will be a useful guideline not only to artistes but vocal teachers and record companies.This journal purposes on the studies of correct vocal singing techniques and knowledge sharing information. The methodology used in this study was throughacquiring vocal aesthetics and improvisations in singing skills from gifted singers derived through interviewsfromsome of Malaysia’s mostgifted stars.The discovery of this study with regards to theanalysis on the differentiation of vocal characteristic aims to indicate positive and innovative results against negative and stereotype emulated singing of amateur singers.Through the findings of this research, amateur and aspiring new singers shall be able to learn to sing and perform properly. The main findings and results aretabled from the top to the least based on important tips like feel, innovative methods, techniques and creativity invarious singing performances. Practical contribution of this study will be a useful guideline not only to artistes but vocal teachers and record companies.